2012
DOI: 10.1038/srep00518
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Cariogenic Character in Streptococcus mutans: Horizontal Transmission of Glycosyl Hydrolase Family 70 Genes

Abstract: Acquisition of the ability to produce polysaccharides from sucrose, i.e. the gtf gene encoding glucosyltransferase (GTF), is the key evolutionary event enabling dental biofilm formation by streptococci. To clarify the ancestry of streptococcal GTFs, time of its occurrence, and order of specific events, we investigated the distribution of GTFs among bacteria by phylogenetic analysis of the glycosyl hydrolase family 70 enzymes. We found that streptococcal GTFs were derived from other lactic acid bacteria such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
38
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 33 publications
2
38
0
4
Order By: Relevance
“…Hoshino et al [39] reported the evolution of the cariogenic characteristics of Streptococcus mutans using glucosyltransferase. In that study, a middle catalytic domain (residues 400-900) instead of the 1500-amino acid full-length sequence of glucosyltransferase was used for the alignment, because the rest of the sequence varied enormously among species.…”
Section: Discussionmentioning
confidence: 99%
“…Hoshino et al [39] reported the evolution of the cariogenic characteristics of Streptococcus mutans using glucosyltransferase. In that study, a middle catalytic domain (residues 400-900) instead of the 1500-amino acid full-length sequence of glucosyltransferase was used for the alignment, because the rest of the sequence varied enormously among species.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the four S. criceti strains studied possessed dblA and dblB genes, suggesting that the dblA and dblB regions are conserved in S. criceti. Furthermore, tandemly arranged genes, such as gtfB and gtfC in S. mutans, are considered to have replicated by tandem duplication (Hoshino et al, 2012). Regarding the dblA and dblB genes, orthologous genes were found in S. sobrinus, S. downei and S. criceti (Kojima et al, 2012).…”
mentioning
confidence: 98%
“…Likewise, evolutionary genomic analysis of over 50 sequenced isolates of S. mutans from around the globe led to the conclusion that there was a large expansion in the population and genetic complexity of this species some 5,000 to 10,000 years ago (17). Phylogenetic analyses have also pointed to a strong influence on the genomic composition of S. mutans associated with widespread consumption of refined sucrose during the industrial revolution (18). In particular, it has been suggested that many of the genes responsible for enhanced cariogenicity in S. mutans were introduced into this bacterium via horizontal gene transfer, including the three glucosyltransferase genes, which encode enzymes that produce biofilmpromoting, adhesive glucans (17)(18)(19).…”
mentioning
confidence: 99%
“…Phylogenetic analyses have also pointed to a strong influence on the genomic composition of S. mutans associated with widespread consumption of refined sucrose during the industrial revolution (18). In particular, it has been suggested that many of the genes responsible for enhanced cariogenicity in S. mutans were introduced into this bacterium via horizontal gene transfer, including the three glucosyltransferase genes, which encode enzymes that produce biofilmpromoting, adhesive glucans (17)(18)(19). Therefore, characterization of the effects of sucrose on gene expression and physiology of S. mutans is critical not only to gain a fuller appreciation of how this carbohydrate enhances the cariogenicity of the organism but also to gain insights into niche adaptations that occurred during coevolution with a human host, which can be highly specific to S. mutans and thus lead to new therapeutic or preventive strategies.…”
mentioning
confidence: 99%